Impact of dental implant diameter on the efficiency of fatigue - a systematic review analysis - Mohamed Tharwat Hamed,; Hisham Abdullah Mously,; Moayyad Motaz Ghulman,; Ghada Hussein Naguib, (Journal of the Pakistan Medical Association, 2021)
Objective: The present study explains the success and failure of dental implant diameter on the efficiency of fatigue by conducting a systematic review analysis. Methods: An extensive literature search was conducted to carry out systematic review using different scholarly platforms and libraries. A total of 12 studies published within the past 20-year time (1999-2019) were included following the inclusion and exclusion criteria based on the PRISMA guidelines. Additionally, the study outcomes were evaluated to determine their perceptions regarding the role of dental implant diameter in influencing the implant’s fatigue performance. Results: The implant diameter can be categorized into wide diameter (5-6 mm), regular diameter (3.75-4 mm), and small/narrow diameter (3-3.4 mm). The narrow diameter implants are indicated through thin alveolar ridges and mesiodistal spaces (less than 7 mm). The implants with narrow diameter would offer greater risk of fatigue failure for clinical situations with significant functional loading. No significant differences were found either in success or failure of dental implant diameter on fatigue efficiency after 1-year and 3-year follow-up. Conclusion: The technical complication of dental implant include abutment screw loosening or fracture, abutment and superstructure fracture, and implant body fracture. The study has study has mainly focused on the impact of dental implant diameter on the efficiency of fatigue and reviewed a significant impact of dental implant diameter on the fatigue efficiency. Keywords: Dental Implants, Efficiency, Perception. Continuous...